Specifics of Syntactic Structures Formed on Basis of Contact Location of Conjunction da and Double Conjunction ne... a... - X. Liu (Научный диалог)
The results of the analysis of syntactic constructions based on the contact location of conjunction da and double conjunction ne… a… are presented. The relevance of the study is determined by the active interest of modern linguistics to function words and, more generally, to means of communication, functioning in different semantic structures. The purpose of the study is to identify and describe semantic and syntactic nature of the structures formed on the model da ne … а ... Material source is National Corpus of the Russian language. Scientific novelty consists in the fact that at this moment there are no studies about the ability of the conjunction da to be combined with double or multiple conjunctions. Practical significance of the research is that the results will be used to create the dictionary of function words of the Russian language, as well as in teaching Russian as a foreign language. The article discusses some cases typical to the structures with da ne … а ..., which include pronominal words with the postfix - nibud’ , adjective prostoy and particle prosto , and counting-pronominal adjective odin . It is stated that using typical lexis and semantics of the components of the complex da ne … а ... forms connecting-graded-lookup relationship in the structure of a sentence.